Floods and droughts research progress and its contributions toward sustainability - Muhammad Abrar Faiz; Ning Ma; Farah Naz (Heliyon, 2024)
In 2015, the United Nations General Assembly launched seventeen Sustainable Development Goals (SDGs), aimed at being achieved by 2030. The SDGs 6 (clean water & sanitation) and 13 (climate actions) are two critically important goals concerning water resources that need to be addressed. This study used the Scopus database to explore climate extremes, specifically droughts and floods, in East Asia and highlight the region's efforts and contributions towards achieving SDGs 6 and 13. We found that even before the implementation of SDGs, the topics related to solving the problems of water resources, water quality, and treatment of wastewater using different conceptual models and methodologies were the main concerns in the region. The adoption of SDGs has led to a heightened focus on water and climate sustainability in East Asia, with the considerable surge in climate-related studies after 2019. Under SDG 13, all countries have contributed substantially to climate action research. Keyword analysis indicates that climate change, water management, water treatment, water quality, and adsorption remain prominent. SDGs 6 and 13 have emerged as crucial areas of focus for research and initiatives as the global community grapples with escalating water resources and climate challenges. Under specific keywords search, China has 2nd place in the search with climate and water during the SDGs period, accounting for 21 % of the entire publication from 2015 to 2023. Japan and South Korea account for of 4 % and 3 %, respectively. The research on floods and droughts has garnered significant attention, with half of the ten highly co-cited literature examining the changing pattern of drought, the influence of extreme events on crop yield, and other related topics. Despite the positive contribution of the East Asia region towards SDGs 6 and 13, there is still an urgent need for a more robust framework to improve the complex interconnections between climate actions, clean water, and sanitation for a sustainable soil-water-plant-atmosphere ecosystem.